APLIKASI INFORMASI DIGITAL FAKULTAS ILMU KOMPUTER UNIVERSITAS MUSLIM INDONESIA - Tanti, Tri Gustanti (JNSTA ADPERTISI JOURNAL, 2024)
The selection of the appropriate information media is very important in supporting the success of delivering information to those concerned, including the Faculty of Computer Science, University of Muslim Indonesia.Furthemore, this research is made with the title "Digital Information Application Based on Website at FIKOM – UMI " to facilitate the delivery of information from faculty staff, study program staff, lecturers and faculty leaders to students to be more efficient in terms of costs, media used to the effectiveness of delivering and receiving information.This system is designed using UML modeling. Meanwhile, the programming language used is PHP and MySQL database.The information contained is the applicable regulations, agenda or event, today's lecture status, lecturers present today, articles that support academic knowledge and all academic and non-academic information deemed necessary to be conveyed to students.